Asperger syndrome - Gillard, Arthur (Perspectives on diseases and disorders, 2011)
"Asperger Syndrome: Understanding Asperger Syndrome; Controversies About Asperger Syndrome; Personal Experiences with Asperger Syndrome"-- Provided by publisher